2012
DOI: 10.5194/acp-12-1951-2012
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend and sources of speciated atmospheric mercury at Waliguan GAW station, Northwestern China

Abstract: Abstract. Measurements of speciated atmospheric mercury were conducted at a remote mountain-top station (Waliguan (WLG) Baseline Observatory) at the edge of northeastern part of the Qinghai-Xizang Plateau, Western China. Mean concentrations of total gaseous mercury (TGM), particulate bound mercury (PBM), and gaseous oxidized mercury (GOM) during the whole sampling campaign were 1.98 ± 0.98 ng m −3 , 19.4 ± 18.1 pg m −3 , and 7.4 ± 4.8 pg m −3 , respectively. Levels of speciated Hg at WLG were slightly higher t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
115
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 52 publications
13
115
2
Order By: Relevance
“…The GOM/PBM concentrations in winter and in spring were not significantly different from each other (t test). Using the same speciation measurements, the concentrations of GOM at DAO are similar to those observed elsewhere, while the concentrations of PBM at DAO are much higher than the concentrations measured at remote sites and urban/suburban areas [Choi et al, 2008;Engle et al, 2010;Fu et al, 2012a;Sigler et al, 2009]. The GOM and PBM concentrations are possibly influenced by local anthropogenic Hg sources during the sampling period.…”
Section: Atmospheric Concentrations Of Tgm Gom and Pbmsupporting
confidence: 51%
See 4 more Smart Citations
“…The GOM/PBM concentrations in winter and in spring were not significantly different from each other (t test). Using the same speciation measurements, the concentrations of GOM at DAO are similar to those observed elsewhere, while the concentrations of PBM at DAO are much higher than the concentrations measured at remote sites and urban/suburban areas [Choi et al, 2008;Engle et al, 2010;Fu et al, 2012a;Sigler et al, 2009]. The GOM and PBM concentrations are possibly influenced by local anthropogenic Hg sources during the sampling period.…”
Section: Atmospheric Concentrations Of Tgm Gom and Pbmsupporting
confidence: 51%
“…The TGM concentration was 3.3 ± 1.4 ng m À3 , higher than the concentrations observed at most remote sites in Europe and U.S. (<2 ng m À3 ) [Choi et al, 2008;Engle et al, 2010;Kock et al, 2005;Sigler et al, 2009] and in SW and NW China (1.6-2.6 ng m À3 ) [Fu et al, 2010[Fu et al, , 2012a[Fu et al, , 2012b, but lower than the concentrations observed at urban sites in China (e.g., 4.9-8.3 ng m À3 in Beijing, 13.5 ± 7.1 ng m À3 in Guangzhou, 5.4 ± 4.1 ng m À3 in Yangtze River Delta, and 3.8 ± 1.3 ng m À3 in Ningbo) [Wang et al, 2007;Nguyen et al, 2011]. The elevated mean concentration suggests the influence from local and regional Hg emissions, with possible contributions from industrial processes (including power plants, steel plants, and cement plants) and domestic heating in industrial/urban areas in Eastern China.…”
Section: Atmospheric Concentrations Of Tgm Gom and Pbmmentioning
confidence: 98%
See 3 more Smart Citations